The Recent Development of Islamic Economic Studies in Indonesia - Ahmad Farras Adibuddin; Doddy Setiawan; Bambang Sutopo (Shirkah: Journal of Economics and Business, 2019)
This study outlines the recent development of Islamic economics in Indonesia. The data has been gathered from articles on Islamic economics published in the select national accredited journals in Indonesia from 2004 – 2017, consisting of 184 articles. This study has applied the field method chart as suggested by Hesford. We have classified these articles based on the field of research, the research topic, and its method. This study finds that there is an increase number of articles on Islamic economics in Indonesia published on national-accredited journals. These selected articles mostly discussed such topics relating to the banking issues. Keywords: Islamic economics, bibliography, analytical method, literature studies, survey method.